2010
DOI: 10.1002/dvdy.22175
|View full text |Cite
|
Sign up to set email alerts
|

Comparative evaluation of human embryonic stem cell lines derived from zygotes with normal and abnormal pronuclei

Abstract: Human embryonic stem (hES) cell lines have been derived from normally or abnormally fertilized zygotes. However, the similar and different properties of these two types of hES cell lines are not well-known. To address this question, we generated nine hES cell lines from zygotes containing normal (2PN) and abnormal (0PN, 1PN, 3PN) pronuclei. A side-by-side comparison showed that all cell lines exhibited distinct identity and karyotypical stability. They expressed similar ''stemness'' markers and alkaline phosph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
24
1

Year Published

2012
2012
2016
2016

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 17 publications
(29 citation statements)
references
References 22 publications
(25 reference statements)
4
24
1
Order By: Relevance
“…The data suggested the following: (1) the diploid hESC lines originated from the tripronucear zygotes that arose from the third pattern of division; and (2) the in vitro selection favored diploid cells. This is in accordance with previously reported results [11,12,29]. The present report is, we believe, the first record of deriving normal and abnormal hESC lines from 3PN zygotes and comparing the characteristics of these two kinds of hESC lines.…”
Section: In Vitro and In Vivo Differentiation Potential Of The Hesc Linesupporting
confidence: 94%
See 4 more Smart Citations
“…The data suggested the following: (1) the diploid hESC lines originated from the tripronucear zygotes that arose from the third pattern of division; and (2) the in vitro selection favored diploid cells. This is in accordance with previously reported results [11,12,29]. The present report is, we believe, the first record of deriving normal and abnormal hESC lines from 3PN zygotes and comparing the characteristics of these two kinds of hESC lines.…”
Section: In Vitro and In Vivo Differentiation Potential Of The Hesc Linesupporting
confidence: 94%
“…Our results suggested that in the modified culture medium the developmental potential of the 3PN zygotes was lower than that of control group, but the efficiency of the hESC derivation was similar in the two group. According to the data in those publications [10][11][12], there is also no difference in the derivation efficiency of hESCs from mononuclear and tripronuclear zygotes between our lab and other labs ( Table 2).…”
Section: In Vitro and In Vivo Differentiation Potential Of The Hesc Linesupporting
confidence: 50%
See 3 more Smart Citations